2009
DOI: 10.1038/ki.2009.11
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical characteristics associated with glomerular filtration rates in living kidney donors

Abstract: Due to the shortage of organs, living donor acceptance criteria are becoming less stringent. An accurate determination of the glomerular filtration rate (GFR) is critical in the evaluation of living kidney donors and a value exceeding 80ml/min per 1.73m2 is usually considered suitable. To improve strategies for kidney donor screening, an understanding of factors that affect GFR is needed. Here we studied the relationships between donor GFR measured by 125I-iothalamate clearances (mGFR) and age, gender, race, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
146
6
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(168 citation statements)
references
References 46 publications
9
146
6
7
Order By: Relevance
“…During its development and validation, Matsuo et al 2) mentioned that the eGFR according to the Japanese GFR equation might not be applicable to the healthy population, because the equation was derived mostly from patients with CKD. Some studies assessed the bias of the above equation by comparing eGFR and measured GFR (mGFR) in renal transplant donor candidates 13,14) . Horio et al described that eGFR was significantly lower than mGFR in potential kidney donors 14) .…”
Section: Discussionmentioning
confidence: 99%
“…During its development and validation, Matsuo et al 2) mentioned that the eGFR according to the Japanese GFR equation might not be applicable to the healthy population, because the equation was derived mostly from patients with CKD. Some studies assessed the bias of the above equation by comparing eGFR and measured GFR (mGFR) in renal transplant donor candidates 13,14) . Horio et al described that eGFR was significantly lower than mGFR in potential kidney donors 14) .…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study, Rule et al [24] reported that GFR decreases at a rate of about 4 mL/min/ 1.73 m 2 per decade of life in prospective donors. Poggio et al [4] also reported that GFR declines at a rate of approximately 4 mL/min/1.73 m 2 per decade of life in donors aged 45 years or younger but the GFR decreases at a faster rate (approximately 8 mL/min/1.73 m 2 per decade) in older donors. Sex and race appear not to be determinants of GFR.…”
Section: Donor Kidney Function and Its Implications To The Donormentioning
confidence: 99%
“…Recent practice in the USA reveals that approximately 67 % of transplant centers use the straight cut-off value of 80 mL/min to accept donors, while 25 % use an age-and sex-based approach [12]. It is necessary to emphasize that because GFR is known to decline with aging, the lower limit of normal GFR in subjects medically cleared to donate a kidney is variable [4]. This is an important issue to keep in mind when evaluating young donors, as a simple cut-off of 80 mL/min may represent low kidney function in such a candidate.…”
Section: Donor Kidney Function and Its Implications To The Donormentioning
confidence: 99%
See 1 more Smart Citation
“…The problem with defining CKD by abnormal levels of GFR is that the GFR threshold varies by method. For example, the fifth percentile for eGFR Cr is about 10 to 15 ml/min per 1.73 m 2 lower than the fifth percentile for mGFR (50). We would define CKD by an elevated serum creatinine level relative to a health-associated reference ranges (e.g., 0.6-1.1 mg/dl in women and 0.8-1.3 mg/dl in men).…”
Section: Practical Implicationsmentioning
confidence: 99%